RETHINKING SOCIAL EXCHANGE IN CYBER PROSTITUTION: POWER ASYMMETRY AND LEGAL FRAGMENTATION IN INDONESIA - M. Hendri Agustiawan; Nazhifatum Mutahhirah; Djody Firmansyah (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
Cyber prostitution in Indonesia has expanded alongside the growth of digital platforms, transforming conventional prostitution into a decentralised and technologically mediated system involving pimps, sex workers, clients, and digital intermediaries. This study examines how Indonesian criminal law regulates cyber prostitution and analyses the power-dependence relations underlying exchanges among these actors through a critical application of Social Exchange Theory. It employs a critical and interdisciplinary doctrinal legal method combining statutory, conceptual, and theoretical approaches. Primary legal materials consist of Indonesian legislation and relevant international instruments, while secondary materials include scholarly literature, institutional reports, and prior empirical studies used as contextual evidence. The study finds that Indonesia lacks a coherent and integrated legal framework specifically addressing cyber prostitution. Relevant provisions remain dispersed across the Criminal Code, the Electronic Information and Transactions Law, the Pornography Law, the Anti-Trafficking Law, the Child Protection Law, and the Sexual Violence Crimes Law. This fragmentation generates conceptual overlap, normative ambiguity, evidentiary difficulties, and uneven criminal accountability. The analysis further shows that classical formulations of Social Exchange Theory, centred on rational choice, reciprocity, and voluntary exchange, are insufficient to explain relationships shaped by structural vulnerability and unequal control over resources. Poverty, gender inequality, limited education, precarious employment, stigma, and restricted alternatives constrain individual agency, while pimps may control clients, prices, digital access, accommodation, protection, information, and emotional resources. These conditions produce asymmetric exchanges in which sex workers bear disproportionate legal, social, health, and psychological costs. The study argues that cyber prostitution should be understood as a digitally mediated and structurally conditioned form of unequal exchange. It concludes that Indonesia requires a technologically responsive, victim-centred, and proportionate legal framework that distinguishes consent from exploitation, differentiates responsibility among actors, strengthens digital investigative capacity, and integrates criminal law reform with social protection, gender-responsive policy, education, and economic empowerment.